Martin Bridge on the lookout! - Kerrin, Jessica Scott (Kids Can Press, 2005)
Three more stores of Martin's plans unravelling. This time, he has to entertain an unwanted guest, share lunch with a boy who eats erasers and embark on a madcap search for his school's escaped pet parakeet.